Mixed Matrix Membrane with Penetrating Subnanochannels: A Versatile Nanofluidic Platform for Selective Metal Ion Conduction. (7th December 2022) - Li, Chen; Jiang, Yanan; Wu, Zihan; Zhang, Youcai; Huang, Cheng; Cheng, Sha; You, Ya; Zhang, Pengchao; Chen, Wen; Mao, Lanqun; Jiang, Lei
Abstract: Biological ion channels penetrated through cell membrane form unique transport pathways for selective ionic conductance. Replicating the success of ion selectivity with mixed matrix membranes (MMMs) will enable new separation technologies but remains challenging. Herein, we report a soft substrate‐assisted solution casting method to develop MMMs with penetrating subnanochannels for selective metal ion conduction. The MMMs are composed of penetrating Prussian white (PW) microcubes with subnanochannels in dense polyimide (PI) matrices, achieving selective monovalent metal ion conduction. The ion selectivity of K + /Mg 2+ is up to 14.0, and the ion conductance of K + can reach 45.5 μS with the testing diameter of 5 mm, which can be further improved by increasing the testing area. Given the diversity of nanoporous materials and polymer matrices, we expect that the MMMs with penetrating subnanochannels could be developed into a versatile nanofluidic platform for various emerging applications. Abstract : Inspired by the unique structure of cell membranes, a mixed‐matrix membrane (MMM) with penetrating subnanochannels was developed based on a soft‐substrate assisted solution casting method for selective conduction of monovalent metal ions. Thanks to the diversity of nanoporous materials and polymer matrix, we expect that the penetrating MMMs could be developed into a versatile nanofluidic platform and offer new possibilities for practical applications.